A General, Fast, and Robust Implementation of the Time-Optimal Path Parameterization Algorithm - Pham, Quang-Cuong (IEEE transactions on robotics, 2014)
Finding the time-optimal parameterization of a given path subject to kinodynamic constraints is an essential component in many robotic theories and applications. The objective of this paper is to provide a general, fast, and robust implementation of this component. For this, we give a complete solution to the issue of dynamic singularities, which are the main cause of failure in existing implementations. We then present an open-source implementation of the algorithm in C++/Python and demonstrate its robustness and speed in various robotics settings.